CYP1A1 Is a Useful Diagnostic Marker for Angiofibroma of Soft Tissue. (6th May 2023) - Uemura, Kotaro; Komatsu, Masato; Hara, Shigeo; Kawamoto, Teruya; Bitoh, Yuko; Itoh, Tomoo; Hirose, Takanori
Abstract : Angiofibroma of soft tissue (AFST) is a recently described benign fibroblastic neoplasm composed of uniform bland spindle cell proliferation in fibrous and fibromyxoid stroma with prominent thin-walled small branching vessels. A major recurrent genetic abnormality in AFST is t(5;8)(p15;q13), which results in the rearrangement of AHRR and NCOA2 . Owing to a lack of discriminatory IHC markers and potential overlap with other mesenchymal neoplasms, it may be difficult to confirm the diagnosis of AFST in some cases. Triggered by a recent gene expression profile study of AFST, which showed the significant upregulation of AhR/AHRR/ARNT downstream genes (including CYP1A1 ), we used a mouse monoclonal antibody to explore the diagnostic significance of CYP1A1 expression in histologically confirmed AFST cases along with 224 control cases, consisting of 221 neoplastic mimickers and 3 non-neoplastic lesions. We found moderate to strong cytoplasmic expression of CYP1A1 in 13 of 16 AFST cases (sensitivity, 81.3%). In contrast, the vast majority of other examined histologic mimickers exhibited no expression of CYP1A1 (specificity, 97.3%), except for 3 myxofibrosarcomas (3/31), 2 solitary fibrous tumors (2/22), and 2 neurofibroma (1/27). Our results indicate that CYP1A1 immunohistochemistry may aid in the diagnosis of AFST by distinguishing among various kinds of tumors, particularly those harboring prominent vasculature.